A Novel Role of Globular Adiponectin in Treatment with HFD/STZ Induced T2DM Combined with NAFLD Rats - Hong Ma; Guo-Ping You; Xuan-Pu Zhang; Xiang-Jiu Yang; Hua-Dong Lu; Yan-Ling Huang; Wen-Qiang Zhang (The Scientific World Journal)
Aims. To evaluate the effects of globular adiponectin (gAd) on treatment of type 2 diabetic rats combined with NAFLD. Materials and Methods. Twenty-one male wistar rats were fed with normal diet (7 rats) or high fat diet (HFD) (14 rats) for 4 weeks, and then HFD-fed rats were injected with streptozotocin (STZ) to induce type 2 diabetes mellitus (T2DM). Half of T2DM rats were randomly injected with gAd intraperitoneally for 7 days. The expressions of adiponectin receptors (adipoR1/R2) in liver and skeletal muscle tissues were detected through western blotting or RT-qPCR, respectively. Results. Globular adiponectin alleviated the hepatic steatosis and increased insulin secretion. In liver, both the protein and mRNA expressions of adipoR2 in T2DM group decreased (P<0.05, resp.) in contrast to NC group and increased (P<0.05 and P<0.001, resp.) after gAd treatment. But the protein and mRNA expressions of adipoR1 increased (P<0.05, resp.) in T2DM group and no change was found in the gAd-treated group. In skeletal muscle, the protein and mRNA expressions of adipoR1 and adipoR2 were upregulated in T2DM group and were downregulated after gAd treatment. Conclusions. Globular adiponectin could ameliorate the hepatic steatosis and vary the expressions of adiponectin receptors in liver and skeletal muscle by stimulating insulin secretion.